39th European Conference and Exhibition on Optical Communication (ECOC 2013) 2013
DOI: 10.1049/cp.2013.1272
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Few-Mode Fibers for Space-Division Multiplexed Transmissions

Abstract: A review of the most recent advances on both weakly-coupled and strongly-coupled fewmode fibers is presented. The challenge of increasing the number of LP modes that can actually be used is also discussed. IntroductionSpace-division-multiplexed transmissions using Few-Mode Fibers (FMFs) have recently received considerable attention because of their potential to multiply the capacity of single-mode transmissions by more than a tenfold.A first weakly-coupled approach 1-5 consists of minimizing mode coupling so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…This optimization, however, becomes more and more difficult when the number of LP modes increases and when one wants to ensure low bend losses (<10 dB/turn at 10 mm radius). We have found that DMGDs become >100 ps/km as soon as the number of LP modes is ≥4 [18].…”
Section: A Design Strategymentioning
confidence: 80%
See 3 more Smart Citations
“…This optimization, however, becomes more and more difficult when the number of LP modes increases and when one wants to ensure low bend losses (<10 dB/turn at 10 mm radius). We have found that DMGDs become >100 ps/km as soon as the number of LP modes is ≥4 [18].…”
Section: A Design Strategymentioning
confidence: 80%
“…Graded-index-core profiles are nevertheless well adapted to low-DMGD FMFs [7]- [10], [18], [20]. Fig.…”
Section: A Design Strategymentioning
confidence: 87%
See 2 more Smart Citations
“…Despite these significant advances, the capacity of optical fibers is expected to reach its limit unless other multiplexing strategies, such as mode division multiplexing (MDM) with multiple-input multiple-output (MIMO) digital signal processing, are considered [1]. Performance optimization of MDM transmissions requires management of channel parameters [3] for which precise knowledge of the LP mode characteristics, including their group delay (GD), dispersion (GVD) and mode-dependent loss, is particularly important. Different methods have been proposed to characterize LP modes of few mode fibers (FMF).…”
Section: Introductionmentioning
confidence: 99%